A mixed-methods evaluation of a multidisciplinary point of care ultrasound program. (1st February 2019) - Smith, Andrew; Parsons, Michael; Renouf, Tia; Boyd, Sarah; Rogers, Peter
Abstract: Background: Point of Care Ultrasound (PoCUS) is well established within emergency medicine, however, the availability of formal training for other clinical disciplines is limited. Memorial University has established a cost-efficient, multidisciplinary PoCUS training program focusing on training residents' discipline-specific ultrasound skills. This study evaluates the skills, knowledge, and attitudes of residents who participated in the program. Methods: Analysis was conducted using a mixed-methods, sequential exploratory approach. Initially, a focus group of seven first year residents was conducted to generate themes that were used to guide development of a survey administered to residents over a two-year period. Results: Thirty residents responded to the survey (response rate 63.8%) with 53.3% meeting the training requirements for focused assessment using sonography in trauma, 43.3% for pleural effusion, 40.0% for aortic aneurysms, and 40.0% for cardiac scans. Early pregnancy assessment was the skill of least interest with 46.6% not interested. Over half the residents (53.6%) agreed or strongly agreed that a multidisciplinary program met their needs while 21.4% disagreed. The focus group found the multidisciplinary approach adequate. Conclusions: A single PoCUS curriculum has been shown to meet the needs and expectations of a majority of residents from multiple disciplines. It can enhance collaboration and bridge gaps between increasingly compartmentalized practices of medicine.